Genetic variation in the alternative splicing regulator RBM20 is associated with dilated cardiomyopathy - Refaat, Marwan M.; Lubitz, Steven A.; Makino, Seiko; Islam, Zahid; Frangiskakis, J. Michael; Mehdi, Haider; Gutmann, Rebecca; Zhang, Michael L.; Bloom, Heather L.; MacRae, Calum A.; Dudley, Samuel C.; Shalaby, Alaa A.; et al. (Heart rhythm, 2012)
Dilated cardiomyopathy (DCM) is a leading cause of heart failure and death. The etiology of DCM is genetically heterogeneous. We sought to define the prevalence of mutations in the RNA splicing protein RBM20 in a large cohort with DCM and to determine whether genetic variation in RBM20 is associated with clinical outcomes. Subjects included in the Genetic Risk Assessment of Defibrillator Events (GRADE) study were aged at least 18 years, had an ejection fraction of ≤30%, and an implantable cardioverter-defibrillator (ICD). The coding region and splice junctions of RBM20 were screened in subjects with DCM; 2 common polymorphisms in RBM20, rs942077 and rs35141404, were genotyped in all GRADE subjects. A total of 1465 subjects were enrolled in the GRADE study, and 283 with DCM were screened for RBM20 mutations. The mean age of subjects with DCM was 58 ± 13 years, 64% were males, and the mean follow-up time was 24.2 ± 17.1 months after ICD placement. RBM20 mutations were identified in 8 subjects with DCM (2.8%). Mutation carriers had a similar survival, transplantation rate, and frequency of ICD therapy compared with nonmutation carriers. Three of 8 subjects with RBM20 mutations (37.5%) had atrial fibrillation (AF), whereas 19 subjects without mutations (7.4%) had AF (P = .02). Among all GRADE subjects, rs35141404 was associated with AF (minor allele odds ratio = 0.62; 95% confidence interval = 0.44–0.86; P = .006). In the subset of GRADE subjects with DCM, rs35141404 was associated with AF (minor allele odds ratio = 0.58; P = .047). Mutations in RBM20 were observed in approximately 3% of subjects with DCM. There were no differences in survival, transplantation rate, and frequency of ICD therapy in mutation carriers.